Water productivity and yield performances of wheat under different irrigation and tillage treatments - Hasan, Md Mahmudul; Mahmud, Khalid; Islam, Md Nazrul; Sarkar, Pijush Kanti; Shariot-Ullah, Md Shariot-Ullah (Fundamental and Applied Agriculture, 2017)
Considering the ever increasing competition among different water users, improving water use efficiency in agriculture is now a grave concern. Contemplating this, the study was carried out to evaluate the interaction effects of different tillage and irrigation treatments on water productivity as well as yield and yield contributing characters of wheat. The field experiment was laid out in two factors using strip plots arrangement and replicated thrice. Treatment combination comprised of 3 levels of irrigation during wheat growth stages: I1 (17-21 Days after sowing (DAS)), I2 (17-21 DAS + 50-55 DAS) and I3 (17-21 DAS + 50-55 DAS + 75-80 DAS). The tillage treatments were: T1 (bed planting), T2 (power tiller operated seeder), T3 (strip tillage) and T4 (zero/no tillage). The actual water requirement was calculated as the depth of water needed to bring the crop rooting zone to field capacity. Among yield contributing characters of wheat only grains spike-1 and spikes m-2 showed significant change in respect of irrigation and tillage treatments. Regardless of irrigation effects, the highest spikelets were observed in bed planting and the lowest in strip tillage condition. Interaction effects of irrigation and tillage on grain yield of wheat were statistically significant amounting maximum (4.37 t ha-1) in T1I3 and the minimum (2.52 t ha-1) in T4I1. Biological yield parameters were insignificantly influenced by interaction effects of irrigation and tillage. Maximum water productivity of wheat was 2.93 kg m-3 in T4I1 and minimum was 1.47 kg m-3 inT4I3. Water productivity increased due to less seasonal water use and decreased with increased irrigation. Highest water productivity and less total water used were observed in zero tillage due to higher infiltration rate in reduced tillage system. Based on the grain yield and water productivity, best combinations of tillage and irrigation treatments were T1I3 and T4I1, respectively. Regardless of irrigation effect, bed planting can be a good tillage option for wheat cultivation. However, considering water productivity of wheat less tillage operation methods (zero tillage and strip tillage) can also be recommended for water scarce areas.